1.1. Given: (i) \( A=60^{\circ} \) and \( B=30^{\circ} \) (ii) \( A=110^{\circ} \) and \( B=50^{\circ} \) (iii) \( A=225^{\circ} \) and \( B=135^{\circ} \) Use a calculator to evaluate each of the following: (a) \( \cos (A-B) \) (b) \( \cos A-\cos B \) (c) \( \cos A \cdot \cos B+\sin A \cdot \sin B \) \( 1.2 \quad \) Compare the values of \( \cos (A-B) \) with the values of \( \cos A-\cos B \) and \( \cos A \cdot \cos B+\sin A \cdot \sin B \) Using your \( \operatorname{comparison} \) in Question 1.2 ., what general \( \operatorname{conclusion~can~be~made~regarding~} \) \( \cos (A-B), \cos A-\cos B \) and \( \cos A \cdot \cos B+\sin A \cdot \sin B \) for any values of \( A \) and \( B \) ?
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To calculate the specific values for the angles provided: (i) For \( A = 60^{\circ} \) and \( B = 30^{\circ} \): - \( \cos(60^{\circ} - 30^{\circ}) = \cos(30^{\circ}) = \frac{\sqrt{3}}{2} \) - \( \cos 60^{\circ} - \cos 30^{\circ} = \frac{1}{2} - \frac{\sqrt{3}}{2} \approx -0.366 \) - \( \cos 60^{\circ} \cdot \cos 30^{\circ} + \sin 60^{\circ} \cdot \sin 30^{\circ} = \frac{1}{2} \cdot \frac{\sqrt{3}}{2} + \frac{\sqrt{3}}{2} \cdot \frac{1}{2} = \frac{\sqrt{3}}{2} \) (ii) For \( A = 110^{\circ} \) and \( B = 50^{\circ} \): - \( \cos(110^{\circ} - 50^{\circ}) = \cos(60^{\circ}) = \frac{1}{2} \) - \( \cos 110^{\circ} - \cos 50^{\circ} \approx -0.342 - 0.643 = -0.985 \) - \( \cos 110^{\circ} \cdot \cos 50^{\circ} + \sin 110^{\circ} \cdot \sin 50^{\circ} \approx (-0.342)(0.643) + (0.940)(0.766) \approx 0.366 \) (iii) For \( A = 225^{\circ} \) and \( B = 135^{\circ} \): - \( \cos(225^{\circ} - 135^{\circ}) = \cos(90^{\circ}) = 0 \) - \( \cos 225^{\circ} - \cos 135^{\circ} \approx -0.707 - (-0.707) = 0 \) - \( \cos 225^{\circ} \cdot \cos 135^{\circ} + \sin 225^{\circ} \cdot \sin 135^{\circ} = (-0.707)(-0.707) + (-0.707)(0.707) = 0 \) Now comparing the values: For \( (i) \): \( \cos(30^{\circ}) \approx 0.866 \), \( \cos 60^{\circ} - \cos 30^{\circ} \approx -0.366 \), \( \cos 60^{\circ} \cdot \cos 30^{\circ} + \sin 60^{\circ} \cdot \sin 30^{\circ} \approx 0.866 \) For \( (ii) \): \( \cos(60^{\circ}) = 0.5 \), \( \cos 110^{\circ} - \cos 50^{\circ} \approx -0.985 \), \( \cos 110^{\circ} \cdot \cos 50^{\circ} + \sin 110^{\circ} \cdot \sin 50^{\circ} \approx 0.366 \) For \( (iii) \): All values equate to zero: \( \cos(90^{\circ}) = 0 \), \( \cos 225^{\circ} - \cos 135^{\circ} = 0 \), and the product-sum also comes to \( 0 \). General Conclusion: The key takeaway is when you compute \( \cos(A - B) \), it accurately reflects the angle difference, and the other expressions will vary based on the cosines and sines of the original angles. When any angle pair \( (A, B) \) suggests orthogonality (\( A-B=90^{\circ} \)), all expressions will yield the expected behaviors as shown in \( (iii) \). This teaches us the power of the trigonometric identities—they're deeply interwoven in how angles relate!